Ratios of biochemical markers in peritoneal fluid to those in venous blood for the diagnosis of ruptured tubal pregnancy: A prospective study. (March 2017) - Zhu, Xiao-Lu; Xue, Zhuo-Wei; Xu, Yan-Li; Wang, Juan; Ai, Zhi-Hong; Teng, Yin-Cheng
Abstract: Objectives: Ectopic pregnancies are among the leading causes of maternal morbidity and mortality in both developed and emerging nations, but tests for early, accurate, and convenient detection are lacking. Study Design: Between January 2013 and February 2015, 504 women with tubal pregnancy were prospectively recruited, and their clinical characteristics were recorded. Samples of peritoneal fluid were collected by culdocentesis, and venous blood was drawn from the antecubital vein. In samples from each source, levels of the following biochemical markers were measured: cancer antigen 125 (CA125), human chorionic gonadotropin (hCG), progesterone, vascular endothelial growth factor, and creatine kinase. Results: The ratios of biochemical markers in the peritoneal fluid and in the blood ( R p/v ) were calculated. The median of R p/v -CA125 and R p/v -hCG were significantly lower in the ruptured ectopic pregnancy group than in the unruptured group. The optimal cutoff value to detect ectopic pregnancy rupture was 401.5 U/mL as the upper limit for peritoneal CA125, with a sensitivity of 93.5% and specificity of 74.2%. The optimal cutoff value was 18.7 as the upper limit in the peritoneal fluid/blood ratio ( R p/v ) of CA125, with a sensitivity of 77.5% and specificity of 68.4%. Conclusions: In countries with poor access to laparoscopy, culdocentesis is useful. In this study, culdocentesis provided additional information for management of abdominal pain when laparoscopy is not available. The authors propose R p/v cutoff values that can be used conveniently and quickly to diagnose ruptured ectopic pregnancies and bleeding, enabling rapid and appropriate therapeutic responses.